Effects of Covid-19 on the Global Economy - Agarwal, Varsha (International Journal of Novel Research and Development, 2022)
How did the Covid19 pandemic bring the global economy to its knees? This paper dives into the ripple effect of the pandemic on the global economy. This unconstrained pandemic brought life to a standstill for about two years, wreaking havoc all over the globe. We see how pandemics in the past can provide a certain statistical prediction on the impact. We also see which sectors were affected the worst and give an insight into the stock market performance during the pandemic. The coronavirus was a very real and global tragedy and the unpredictability of the consequences made industries everywhere suffer.
ISME
Keywords: Economic crisis; global recession; uncertainty; containment; spillover effect